The Dimensions of the Quality of Financial Reporting and Their Impact on The Performance and Profitability of Companies - Hayder Jameel Ahmed; Sara AbdulalKareem Mohsin (Academia Open, 2025)
Background: High-quality financial reporting is essential for ensuring transparency, reducing information asymmetry, and strengthening stakeholder confidence, yet its direct contribution to firms’ financial performance remains debated. Specific Background: Prior evidence highlights varied effects of reporting quality across sectors and institutional environments, underscoring the need for sector-specific empirical validation in emerging markets such as Iraq. Knowledge Gap: Limited research has examined how reporting quality influences both performance and profitability across multiple Iraqi industries using integrated financial indicators within a multi-year framework. Aims: This study evaluates the effect of financial reporting quality on firms’ performance and profitability among corporations listed on the Iraq Stock Exchange from 2020–2023. Results: Regression analysis demonstrates a strong and significant relationship between reporting quality and key performance measures (ROA, ROE, D/E ratio, current ratio, and EBIT%), with an overall model correlation of 0.692. Sectoral results show that firms with higher and stable reporting quality tend to exhibit stronger or improving profitability, whereas weak reporting quality correlates with declining performance. Novelty: The study integrates four core reporting-quality dimensions with multi-sector financial indicators, providing a holistic assessment rarely conducted in the Iraqi context. Implications: Findings emphasize the strategic value of enhancing reporting quality to improve financial outcomes and guide regulatory, managerial, and policy reforms.Highlight : The content emphasizes how reporting quality influences firms’ profitability through clearer and more reliable financial information. The analysis highlights significant relationships between reporting quality and key performance indicators across sectors. The findings underline that consistent, transparent reporting supports better decision-making for stakeholders Keywords : Financial Reporting, Financial Performance, Financial Reporting Quality, Profitability, Earnings Quality